2016
DOI: 10.15517/rbt.v64i3.22142
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometry of the Revista de Biología Tropical / International Journal of Tropical Biology and Conservation: document types, languages, countries, institutions, citations and article lifespan

Abstract: Abstract:The Revista de Biología Tropical / International Journal of Tropical Biology and Conservation, founded in 1953, publishes feature articles about tropical nature and is considered one of the leading journals in Latin America. This article analyzes document type, language, countries, institutions, citations and -for the first time-article lifespan, from 1976 through 2014. We analyzed 3 978 documents from the Science Citation Index Expanded. Articles comprised 88 % of the total production and had 3.7 cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 36 publications
2
17
0
6
Order By: Relevance
“…This result also fits a pattern reported before that indicates the development of a stronger scientific apparatus in Central America in recent years (Monge-Nájera & Ho, 2016). The "rediscovery" of papers that become highly cited again after decades, is unusual and, in our study of Central American .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result also fits a pattern reported before that indicates the development of a stronger scientific apparatus in Central America in recent years (Monge-Nájera & Ho, 2016). The "rediscovery" of papers that become highly cited again after decades, is unusual and, in our study of Central American .…”
Section: Discussionsupporting
confidence: 91%
“…Studies led by foreigners are more cited than those from Salvadoran scientists because foreign researchers have better access to SCI-EXPANDED journals; and review articles are more cited because they summarize important amount of information; all of these results are similar to previous findings in neighboring countries (Monge-Nájera & Ho, 2012;2016).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…La predominancia de autores de la misma institución que edita la revista, o sea, la UNED costarricense, es también un patrón conocido, por ejemplo, en la Revista de Biología Tropical, que es publicada por la UCR y -predeciblemente--dominada por autores de esa institución (Nielsen-Muñoz et al, 2012;Filippo et al, 2016;Monge-Nájera & Ho, 2016).…”
Section: Discussionunclassified
“…The reason to publish in English, even in journals of Spanish-speaking countries, is that authors must disseminate their results throughout Latin America (Ryder, 2001). However, a recent analysis from The Revista de Biología Tropical/ International Journal of Tropical Biology and Conservation (founded in 1953), which receives manuscripts in several languages, demonstrated that Spanish and English articles were nearly equal in numbers and that citation of English articles was only slightly higher (Monge-Nájera & Yuh-Shan, 2016).…”
Section: Should We? or Can We Publish In English?mentioning
confidence: 99%